Mobility and Frailty Rehabilitation in Older Adults. Issue 2 (April 2023) - Treacy, Daniel; Sherrington, Catherine
Abstract : Mobility is a broad term which is defined as the ability to move around and change positions such as walking, rising from a chair, and maintaining balance while standing. Mobility has been shown to be key determinant in older individuals' overall health and quality of life. High rates of mobility and functional limitation are evident in older people with frailty. Exercise-based rehabilitation interventions including mobility and balance training are effective in improving mobility in individuals with frailty.